An XFEM plate element for high gradient zones resulted from yield lines - Xu, Jin (2014)
A high gradient of displacement field occurs when a yield line is formed in a plate with elasto-plastic material. For such applications, the Extended Finite Element Method (XFEM) has shown to be an effective numerical method to capture the behavior of a plate with a locally non-smooth displacement field, as well as a displacement field with a high gradient. In this article, a 6-node isoparametric plate element with XFEM formulation is presented to capture the elasto-plastic behavior of a plate in small-deformation analyses. The Hermite function is adopted at the element level to enrich both the translational and the rotational displacement approximation fields so that non-smoothness in displacement fields near a yield line can be simulated.